Improvement in Nitrification Through the Use of Natural Zeolite: Influence of the Biomass Concentration and Inoculum Source - Montalvo-Martinez, S (Center for Environmental and Energy Research and Studies, 2014)
A batch nitrification process was studied using synthetic wastewater as substrate and Chilean natural zeolite as biomass carrier at ambient temperatures (20 °C). Three groups of experiments were carried out: a first experimental set (I) with and without added zeolite using initial biomass concentrations of 1,000 and 2,000 mg VSS/L; a second set of experiments (II) with added zeolite and at the same initial biomass concentrations. In these two experimental sets, biomass from an activated sludge process located in an urban wastewater treatment plant at La Farfana, Santiago de Chile, was used as inoculum (1). Finally, a third set of experiments (III) was carried out with zeolite at an initial biomass concentration of 1,000 mg VSS/L using an inoculum derived from an activated sludge process treating wastewater from a paper mill (inoculum 2). Nitrifying biomass concentration values in the range of 13,000-18,800 mg VSS/L were achieved when initial biomass concentrations varied between 1,000 and 2,000 mg VSS/L. Inoculum (1) generated higher biomass concentrations than inoculum (2). Ammonium N removals higher than 70 % were obtained in experimental sets II and III when zeolite was used. For both initial biomass concentrations tested, an exponential biomass growth was observed up to the second day of operation, and a slight decrease was evident afterwards, achieving stationary values after 10-12 days of operation. The third experimental set (III) revealed that the highest N consumption took place between days 11 and 16 of digestion. © 2013 Islamic Azad University (IAU).